2019
DOI: 10.3389/fevo.2019.00458
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Drivers of Pine Processionary Moth Defoliation in Mediterranean Mountain Forests

Abstract: Insect defoliations are one of the threats of forests health, and climate warming may enhance the occurrence of more severe outbreaks. Thus, understanding the spatial and temporal patterns of insect defoliation may provide valuable information to infer their responses to climate change. To contribute to this question, we studied a 42-year long record of defoliation by pine processionary moth (Thaumetopoea pityocampa, hereafter PPM), a major defoliating insect of Mediterranean conifers. We tested the hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Analysis of a longer time frame would surely help defining positive vs. negative gradation phases of PPM populations. For instance, a recent analysis of 42 years in France revealed three mean peaks of PPM activity [51].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of a longer time frame would surely help defining positive vs. negative gradation phases of PPM populations. For instance, a recent analysis of 42 years in France revealed three mean peaks of PPM activity [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, warming may not affect pest outbreak unless it is synchronized with the important phases of the insect's life cycle such as overwintering. In this regard, Gazol et al (2019) showed that only warmer winters affect pine processionary moth, Thaumetopoea pityocampa, outbreak. According to these findings, while warming temperature may increase pest outbreaks, there are also possibilities that this may not always be the case.…”
Section: Insect Pest Outbreakmentioning
confidence: 99%
“…), Scots pine (Pinus sylvestris L.), Aleppo pine (Pinus halepensis Mill) and maritime pine (Pinus pinaster Ait. ), while others such as stone pine (Pinus pinea L.) are less affected (Gazol et al, 2019;Azcaŕate et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still unknown how stressors such as PPM defoliations and drought interact and affect long-term Mediterranean conifer forest dynamics (Linares et al, 2014;Camarero et al, 2022a). To answer this question, tree-ring based reconstructions of insect outbreaks together with geographically detailed and temporally updated field reports of related defoliation are needed (Sangüesa-Barreda et al, 2014;Navarro et al, 2018;Gazol et al, 2019).…”
Section: Introductionmentioning
confidence: 99%